National Development Plan 2014 - 2018 and reactivation agriculture Colombia (2015)
The following work aims to understand the importance and efficiency of state support to the agricultural industry to strengthen the Colombian economy , will look at the evolution of the strategies promoted by the various governments during the last decades , in order to approach a little more to understand if these were in line with the needs that had at the time and look at the current strategies of the National Development Plan in relation to the revival of the agricultural economy . Finally we see a conclusion where we can define whether it is sufficient to strengthen the presence of State policies and subsidies grants of aid to farmers or to implement other strategies more dynamic economy .